PENGARUH MODEL CONTEXTUAL TEACHING AND LEARNING MENGGUNAKAN MEDIA DIGITAL INTERAKTIF TERHADAP PEMAHAMAN KONSEP PENGUKURAN LUAS SISWA KELAS IV SD GUGUS I DI KOTA SAWAHLUNTO - Infia Rahmi, Sabrina; Melva Zainil; Refina Andika; Sahrun Nisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low understanding of mathematical concepts among students, which is caused by teacher-centered learning and limited use of interactive learning media. This study aims to determine the effect of using the CTL learning model with interactive digital media on the understanding of the area measurement concept of fourth-grade students at SD Gugus I in Sawahlunto City. The type of research is quantitative research with a quasi-experimental design using the Non-Equivalent Control Group Design. The research sample consisted of fourth-grade students of SDN 03 Aur Tajungkang as the experimental class and fourth-grade students of SDN 13 Pasar Remaja as the control class, with a total sample of 46 students. Data collection techniques were through tests in the form of pretests and posttests. Data were analyzed using normality tests, followed by hypothesis testing using the Independent Sample T-Test. The research results obtained data with an average student learning outcome in the experimental class of 72.75, while in the control class it was 48.00. The hypothesis test results showed a significance value (Sig. 2-tailed) < 0.001 which means < 0.05, so H₀ is rejected and H₁ is accepted. Thus, it can be concluded that the CTL learning model based on interactive digital media can be used as one of the alternative learning models that is effective in improving students' understanding of mathematical concepts. After conducting the research, the author suggests that in the learning process, the Contextual Teaching and Learning model using interactive digital media can be applied in schools as an interactive learning medium, in order to create a more effective and enjoyable learning atmosphere, thereby impacting better learning outcomes.